Accelerated and Standard Corneal Cross-Linking Protocols in Patients with Down Syndrome: A Non-inferiority Contralateral Randomized Trial - Hassan Hashemi; Kazem Amanzadeh; Mohammad Seyedian; Hojjat Zeraati; Cynthia J. Roberts; Shiva Mehravaran; Renato Ambrósio; Riccardo Vinciguerra; Paolo Vinciguerra; Soheila Asgari (Ophthalmology and Therapy, 2020)
Abstract Introduction To compare the results of an accelerated corneal cross-linking (CXL) protocol (9 mW/cm2, 10 min) with the standard CXL protocol (3 mW/cm2, 30 min) in patients with Down syndrome (DS) who have keratoconus (KC). Methods Twenty-seven 10- to 20-year-old patients with DS who had bilateral progressive KC were enrolled in a contralateral randomized trial and completed 2 years of follow-up examinations. Fellow eyes were randomly allocated to the accelerated CXL group or the standard CXL group. The main outcome measure was change in maximum keratometry (Kmax) centered on the steepest point (zonal Kmax − 3 mm) with a non-inferiority margin of 1.0 diopter (D). Vision and refraction tests, ophthalmic examinations, and corneal tomography were performed at baseline and at 6, 12, and 24 months after CXL. Failure was defined as an increase of ≥ 1.0 D in zonal Kmax − 3 mm within a 12-month period. Results The mean age (± standard deviation) of the patients was 15.71 ± 2.40 years. The within-group change in zonal Kmax − 3 mm was not significant after 2 years in either group, and within-group zonal Kmax − 3 mm remained stable. At 2 years after CXL, the mean change in the zonal Kmax − 3 mm was – 0.02 ± 0.81 D and – 0.31 ± 0.86 D in the accelerated CXL and standard CXL groups, respectively (P = 0.088). At 1 year of follow-up, three patients in the accelerated CXL group showed treatment failure (mean change in zonal K max − 3 mm + 2.12 ± 0.11 D); no patients in the standard CXL group showed treatment failure. At 2 years of follow-up, these three patients showed a decrease of – 0.43 ± 0.18 D in zonal K max − 3 mm from a baseline value of 55.11 ± 0.32 D. The 2-year trends of the inferior–superior asymmetry and vertical coma were statistically significantly different between the two groups, with the accelerated CXL protocol showing superiority in patients with higher baseline values. Conclusion In young patients with Down syndrome, the accelerated CXL protocol was able to halt disease progression and may be an alternative for the standard CXL protocol. In advanced KC, the efficacy of the accelerated approach was delayed and appeared later in the follow-up. In asymmetric cornea, the accelerated CXL resulted in centralization of the corneal cone. Trial Registration Iranian Registry of Clinical Trials, IRCT20100706004333N3